Use Of Sosial Media Youtube For Collaborative Learning - Lestary, Indry Ayu (Apik Cahaya Ilmu, 2024)
The goals of this paper is analyze and evaluate of design instructional video content on the performance of students in collaborative learning methods. Design of video content used the research 3 models are video slides, props and explanations lecturer, tested to student. Using the concept of TAM, visible results from the ease and understanding of the students learning process. Results of the analysis is a video tutorial uses props learning can provide a different effect on the improvement of student learning outcomes than the use of video learning using slides and video that explain the material just same as usual.